2021
DOI: 10.1111/epi.17132
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light as biomarker of seizure‐related neuronal injury in status epilepticus

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 13 publications
6
29
0
Order By: Relevance
“…First, we show that Simoa technology is sensitive and reliable enough to measure NfL in serum as a proxy for CSF in SE. This is a finding in line with the other paper on that topic by Giovannini and colleagues [ 6 ]. In both studies, even though Giovannini used a different method to measure NfL, the correlation between CSF and serum NfL values in SE patients is very similar.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, we show that Simoa technology is sensitive and reliable enough to measure NfL in serum as a proxy for CSF in SE. This is a finding in line with the other paper on that topic by Giovannini and colleagues [ 6 ]. In both studies, even though Giovannini used a different method to measure NfL, the correlation between CSF and serum NfL values in SE patients is very similar.…”
Section: Discussionsupporting
confidence: 93%
“…If future studies confirm that non-convulsive SE too leads to significant neurodestruction, intensified treatment might be indicated. Additional findings are that NfL concentrations in most SE patients are higher than the age-adjusted 95th percentile of neurologically healthy controls which is in agreement with the only other study of NfL in SE [6]. Interestingly, the range of NfL concentrations overlapped between SE and controls also in this study [6].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that the average interictal NF-L levels in patients with drug-refractory epilepsy due to structural and other etiologies, genetic epilepsy, or temporal lobe epilepsy with hippocampal sclerosis are comparable to those in controls, although they can be slightly increased in some subpopulations of patients when using a cut-off level of 10 pg/mL [ 51 , 52 , 53 ]. Other studies, however, reported that patients with post-stroke epilepsy or epilepsy related to auto-immune encephalitis have chronically increased serum NF-L levels, even though the levels remain below 100 pg/mL [ 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported Increased serum NF-L levels in patients with status epilepticus (SE) when assessed within 48 h after the beginning of seizure activity [ 51 ]. In addition, elevated NF-L levels are associated with the development of treatment refractoriness and 30-day clinical worsening or death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation